The combined effect of Cd and high light stress on the photochemical processes in Arabidopsis thaliana - Giordanoj, D; BartáK, M; Hájek, J (Photosynthetica, 2025)
The adverse effects of cadmium on plants are accompanied by a limitation of photosynthesis, due to the production of reactive oxygen species, leading to oxidative damage to PSII and the disruption of key protein complexes involved in photosynthetic pathways. We investigated the effects of cadmium stress combined with high light in Arabidopsis thaliana, as dependent on the cadmium dose applied. The aim was to investigate the combined effect of the two stressors on photochemical processes with the hypothesis that Cd stress enhances the negative effect of the high light. The plants were treated with 0, 1, 10, and 50 mM Cd added as CdCl2 solution to soil (potted plants), and a high light stress. The highest dose (50 mM) induced a significant oxidative stress, reduced chlorophyll fluorescence parameters related to PSII functioning and increased energy dissipation mechanisms. Elevated Cd contents impaired the electron transport and limited PSII efficiency. OJIP analysis revealed a Cd-induced K- and L-band appearance documenting LHC-PSII limitation. The combination of Cd and high light stress resulted in the photoinhibition effects in PSII, i.e., a decrease in potential and effective yields of PSII.
Keywords: oxidační stres; fotosyntéza; Arabidopsis; reaktivní formy kyslíku; Photosynthesis; Chlorophyll; chlorophyll fluorescence; transport elektronů; Stress, Physiological; světlo; Reactive Oxygen Species; Electron Transport; chlorofyl; fotochemické procesy; Photochemical Processes; heavy metal; nonphotochemical quenching; Photosystem II Protein Complex; cadmium; photoinhibition; kadmium; Light; Oxidative Stress; fyziologický stres; OJIP; fotosystém II (proteinový komplex); protective mechanisms; Cadmium